How Financial and Digital Literacy Shape E-Wallet Adoption Decisions - Kiki Kharisma Putri; Friyatmi (Al-Qalam Institue, 2025)
The rapid development of digital financial technology has significantly changed transaction patterns among university students, particularly through the use of e-wallets. The level of adoption of this technology is strongly influenced by individuals' financial literacy and digital literacy. This study aims to analyze the influence of financial literacy and digital literacy on students' decisions to use e-wallets at the Faculty of Economics and Business, Padang State University. This research employed a quantitative approach with an associative design. The sample consisted of 98 students selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that financial literacy and digital literacy simultaneously have a positive and significant effect on the decision to use e-wallets. Partially, both financial literacy and digital literacy also have a significant influence, with digital literacy showing a more dominant effect. These findings highlight the importance of enhancing both digital and financial literacy as a foundation for shaping intelligent and adaptive financial decisions in response to technological developments.